Whole-genome sequencing reveals genomic characterization of Listeria monocytogenes from food in China - Ji, Shunshi; Song, Zexuan; Luo, Lijuan; Wang, Yiqian; Li, Lingling; Mao, Pan; Ye, Changyun; Wang, Yan (Frontiers in Microbiology, 2023)
Listeria monocytogenes is a foodborne bacterium that could persist in food and food processing environments for a long time. Understanding the population structure and genomic characterization of foodborne L. monocytogenes is essential for the prevention and control of listeriosis. A total of 322 foodborne L. monocytogenes isolates from 13 geographical locations and four food sources in China between 2000 and 2018 were selected and subjected to sequenced. By silico subtyping, we found that serogroup IIa was the most prevalent serogroup and ST9 was the most prevalent sequence type in Chinese foodborne L. monocytogenes. The in-depth phylogenetic analysis on clonal complex (CC) 9 revealed that ST122 clone might be original from ST9 clones. Furthermore, 23 potentially relevant clusters were identified by pair-wised whole-genome single nucleotide polymorphism (wgSNP) analysis, indicating that persistent- and/or cross-contamination had occurred in markets in China. L. monocytogenes ST8 and ST121 that were the second and third top sequence types in China had heterogeneity with the non-Chinese isolates. The antibiotic resistance genes aacA4, tetM, tetS, dfrG carried by different mobile elements were found in Chinese L. monocytogenes. One lineage II strain carrying Listeria Pathogenicity Island-3 was reported. In addition, two novel types of premature stop codons in inlA gene were identified in this study. These findings revealed the genomic characteristics and evolutionary relationship of foodborne L. monocytogenes in China, and further confirmed that whole-genome sequencing analysis would be a helpful tool for routine surveillance and source-tracing investigation.